ISLAM AND THE ROLE OF WOMEN IN THE PUBLIC SPHERE - Naning Zuliarti; M. Ziyadul Haq; Ahmad Syukron (PT. Jurnal Center Indonesia Publisher, 2026)
This article examines the role of Muslim women in the public sphere using a systematic literature review approach. By integrating indexed scientific sources, gender theory, and Islamic studies, this research aims to outline the evolution of women’s roles from historical to contemporary perspectives. Historical approaches and methodological frameworks are employed to structure arguments systematically, covering the basic Islamic concept of women’s roles, the methodology applied in the literature review, analysis of social dynamics and relevant case studies, and critical discussion of challenges and opportunities faced by women in the public sphere. This study also identifies internal and external factors that influence women’s roles, ranging from geographical context to public policy developments. The findings show that interpretations of the concept of equality in Islam have shifted over time and are shaped by socio-political dynamics. This research is expected to stimulate further academic debate on women’s roles in the public sphere and contribute to more inclusive policies. This article explores various historical and contemporary dimensions that shape the role of Muslim women in the public sphere, highlighting both the potential and challenges in translating Islamic values of equality into policy and social practice. It is hoped that this study will enrich academic discourse on the relationship between religion, gender, and modernity, and pave the way for policy initiatives that support women’s empowerment in the Islamic world.